Gastos sujetos a límites y su efecto en la determinación del impuesto a la renta de las empresas comerciales de la provincia Chiclayo - 2016 - Silva Vilchez, Diana Carolina (2019)
ABSTRAC The purpose of the investigation was to determine the effect of the expenses subject to limits in the determination of the income tax of the commercial companies of the province of Chiclayo; In the present investigation, 66 commercial companies from the province of Chiclayo were selected through simple random sampling, using the inductive - deductive, descriptive method; A reliable and validated questionnaire was also used to collect the field information; the data obtained were processed through the statistical software. The results are presented in tables and statistical figures determining the effect of the expenses subject to limit. Likewise, an analysis was made of the expenses that were generated in the development of the operations of the companies, in order to determine which expenses are deductible and not deductible and therefore can cause temporary and permanent differences. It is concluded that the effect of the deductible expenses in the determination of the Income Tax of the commercial companies, of the Chiclayo province, 2016, is negative allowing to pay higher income tax. It is recommended that the Tax Administration eliminate the restriction of the expenses subject to limits and accept to deduct all the expenses indicated in Article 37 of the Income Tax without any limitation, for which reason greater control measures would have to be implemented, allow to mitigate the possible abusive use in the deduction of costs or expenses.